Does the exercise order affect body composition in ten weeks of concurrent training? - Bruno Nobre Pinheiro; Lino Scipião Júnior; Paulo André Uchoa; Samuel Brito Almeida; Francisco Dower Barroso; Jurandir Fernandes Cavalcante; Victor Machado Reis; José Vilaça-Alves (Desafio Singular, 2019)
This study aimed to observe if the order of the predominantly aerobic exercise, concerning the predominantly anaerobic exercises, in the concurrent training affects the body composition. Nine young males and nine young females were equitably dived into three groups that performed for ten weeks a concurrent training, differing between them in the order of the predominantly aerobic exercise in relation to the predominantly anaerobic exercises, with the objective to change the body composition: i) before; ii) after; and iii) interleaved. The measurements of the body composition were performed before (T0) and after ten weeks (T1) of concurrent training, a protocol using the dual-energy x-ray absorptiometry (DXA). It was observed a significant (p<0.05) reduction in the percentage of total body fat in all groups (25.75±9.34 to 25.08±9.38, 26.08±8.17 to 25.51±7.54, 28.20±4.29 to 26.45±5.56, T0 and T1, before, after and, interleaved, respectively). The total fat-free mass it was significantly increased in the after order group (50.74±11.82 kg to 51.01±11.85 kg, T0, and T1, respectively) and the upper limbs fat-free mass also significantly increased only in the before order group (6.66±2.64kg to 7.15±2.95kg, T0, and T1, respectively). No statistical differences were observed in any study variables between groups. Based on the data of the present study, the order of the predominantly aerobic exercise concerning the predominantly anaerobic exercises in the concurrent training did not influence the alterations in the body composition.